Nazhariyah Noam Chomsky fii An-Numu Al-Lughawi wa In’ikasatuha ‘ala Ta’lim Al-Lughah Al-Arabiyah - Anita Andriya Ningsih; Muhammad Mubasysyir Munir; Mustapa Mustapa (Rumah Jurnal IAIN Bukittinggi, 2021)
Chomsky argues that the language is too complicated to learn through passages, such as studying city rosters around the world. Since the early 1970s, theoretical disciplines and teaching methodologies have continuously sought to realize their symbiotic relationships. Teaching language within the framework of Chomsky's theory should give students an appropriate linguistic description with due regard to the student's intellectual level. Language is not only a device for capturing information from what it has learned, but in fact it returns to the student's mental and cognitive ability to complete the process.يرى تشومسكي بأن اللغة معقدة للغاية بحيث لا يمكن تعلمها من خلال المقاطع ، مثل دراسة قوائم المدن حول العالم. منذ أوائل السبعينيات ، سعت التخصصات النظرية ومنهجيات التدريس باستمرار إلى إدراك علاقاتها التكافلية. يجب أن تعطي لغة التدريس في إطار نظرية تشومسكي للطلاب وصفًا لغويًا مناسبًا مع إيلاء الاعتبار الواجب للمستوى الفكري للطالب. اللغة ليست فقط أداة لالتقاط المعلومات مما تعلموه ، ولكنها في الواقع تعود إلى قدرة الطالب العقلية والمعرفية لإكمال العملية.